Adaptive Governance: Islamic Financial Institutions Governance in Realizing Green Banking in Aceh - Kamaly, Nurul; afrijal, afrijal; Usman, Bustami; agustina, soraya; Khaira, Raudhatul; Herizal, Herizal (Universitas Teuku Umar, 2025)
Climate change and the impacts of globalization significantly influence contemporary environmental life systems. Environmental degradation represents a challenge confronted by every nation, not solely due to climate change effects but exacerbated by human interventions. This research examines the implementation of adaptive governance within Islamic financial institutions in Aceh to realize the green banking concept. The study employs mixed methods, focusing on the effectiveness of Qanun Number 11 of 2018 regarding Financial Institutions in supporting sustainable banking practices. Through in-depth interviews with stakeholders from various Islamic banks and descriptive statistical analysis, the research reveals that Islamic financial institutions in Aceh have demonstrated positive contributions to the green banking concept. Research findings indicate that Shariah-based policy frameworks possess significant potential in promoting environmentally friendly financial practices, although further strengthening remains necessary in socialization aspects and corporate social responsibility (CSR) program optimizationClimate change and the impacts of globalization significantly influence contemporary environmental life systems. Environmental degradation represents a challenge confronted by every nation, not solely due to climate change effects but exacerbated by human interventions. This research examines the implementation of adaptive governance within Islamic financial institutions in Aceh to realize the green banking concept. The study employs mixed methods, focusing on the effectiveness of Qanun Number 11 of 2018 regarding Financial Institutions in supporting sustainable banking practices. Through in-depth interviews with stakeholders from various Islamic banks and descriptive statistical analysis, the research reveals that Islamic financial institutions in Aceh have demonstrated positive contributions to the green banking concept. Research findings indicate that Shariah-based policy frameworks possess significant potential in promoting environmentally friendly financial practices, although further strengthening remains necessary in socialization aspects and corporate social responsibility (CSR) program optimization.